The mediating role of innovation on the relationship between knowledge sharing and operational performance : a study of co-operative sector in Kota Kinabalu, Sabah - Eng, Keng Seng (2016)
There are very few studies conducted to measure the impact of knowledge sharing towards performance of an organization, especially with innovation serve as the mediating variable in the research at the same time. The purpose of this study is to examine the influence of knowledge sharing and innovation towards operational performance. This study is based on a survey of 112 co-operative board members in Kata Kinabalu, Sabah, with one co-operative represented by one member from the co-operative board. Structural Equation Model (Partial Least Square approach, version 2.0) is applied for hypothesis testing. Results showed that knowledge sharing will influence the organizational performance, however only in terms of explicit knowledge sharing. Sharing of both knowledge are founded to be able to influence the innovation, where innovation also positively related to organizational performance. Innovation has proven to have mediating effect on the relationship between knowledge sharing and organizational performance, however the effect is only found towards relationship between explicit knowledge sharing and performance.